Recombinant Adeno-Associated Virus-Mediated In Utero Gene Transfer Gives Therapeutic Transgene Expression in the Sheep - Abi Nader, Khalil (2011)
Somatic in utero gene therapy aims to treat congenital diseases where pathology develops in perinatal life, thereby preventing permanent damage. The aim of this study was to determine whether delivery of self-complementary (sc) adeno-associated virus (AAV) vector in utero would provide therapeutic long-term transgene expression in a large animal model. We performed ultrasound-guided intraperitoneal injection of scAAV2/8-LP1-human Factor IX (hFIX)co (1 × 1012 vector genomes/kg) in early (n = 4) or late (n = 2) gestation fetal sheep. The highest mean hFIX levels were detected 3 weeks after injection in late gestation (2,055 and 1,687.5 ng/ml, n = 2) and 3 days after injection in early gestation (435 ng/ml, n = 1). Plasma hFIX levels then dropped as fetal liver and lamb weights increased, although low levels were detected 6 months after late gestation injection (75 and 52.5 ng/ml, n = 2). The highest vector levels were detected in the fetal liver and other peritoneal organs; no vector was present in fetal gonads. hFIX mRNA was detectable only in hepatic tissues after early and late gestation injection. Liver function tests and bile acid levels were normal up to a year postnatal; there was no evidence of liver pathology. No functional antibodies to hFIX protein or AAV vector were detectable, although lambs mounted an antibody response after injection of hFIX protein and Freund's adjuvant. In conclusion, hFIX expression is detectable up to 6 months after delivery of scAAV vector to the fetal sheep using a clinically applicable method. This is the first study to show therapeutic long-term hFIX transgene expression after in utero gene transfer in a large animal model.